Facebook, Is It Really Worth Advertising Here? A Study Based on The Views of The Students Studying at the University of Nottingham - Fernandes, Francis John (2011)
Having been launched as a site only for college students, Facebook has emerged as a networking site that is open to people spread across the world. Facebook does not charge anyone to gain membership instead it earns its revenues through the advertisements that are displayed on the site. Therefore, this study will focus on understanding whether it is worth the investment that organisations risk by advertising on Facebook. This paper therefore explores the effectiveness of advertising on Facebook, especially focussing on the students at the University of Nottingham. The research was conducted by running a survey on Facebook where 77 participants responded to it. In addition to the survey, in-depth interviews were conducted in order to gain a much deeper insight to the research. The survey found out that hardly anyone paid much attention to the advertisements on the site due to their poor targeting services. Also, women were more interested in online activities compared to men. The online and offline mediums of advertising were both considered equally important in delivering the services to their target audience and no particular medium was preferred over the other. Google was considered the best source of seeking information online. Finally, Facebook was regarded as a good source of generating word of mouth publicity which helps in attracting new consumers. At the same time, managerial implications are provided in order to gain insights about this study and finally future research will help in determining whether the results we found are relevant and applicable to a wider target audience.